2020
DOI: 10.3390/antiox9020131
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Fractions from Dandelion Leaves and Petals as Modulators of the Antioxidant Status and Lipid Profile in an In Vivo Study

Abstract: Alcoholic leaf and petal fractions of Taraxacum officinale (dandelion) were previously demonstrated to exert in vitro antioxidant and antithrombotic activities in blood plasma and platelets. Eight-week-old male Wistar rats (n = 6) were supplemented for four weeks with dandelion fractions (694 mg/kg of diet = 11.9 ± 0.6 mg daily). Dandelion leaf and petal fractions, which delivered daily 4.10 ± 0.05 and 1.41 ± 0.07 mg l-chicoric acid, respectively, were shown to exert antioxidative actions, measured as decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 33 publications
(69 reference statements)
1
25
0
6
Order By: Relevance
“…For instance, Silybum marianum (milk thistle) and its main constituent silymarin (rich in flavolignans) ( 14 ) have been shown to reduce plasma and liver markers of inflammation in high-fat diet (HFD)-fed mice ( 15 ). Similarly, Taraxacum officinale (dandelion) extracts have been shown to reduce LPS-induced inflammation in endothelial cells ( 16 ) and macrophages ( 17 ) and have cholesterol-modulating effects in rodents ( 18 , 19 ) and type 2 diabetic patients ( 20 ). Likewise, Avena sativa (oat) is well-known for its anti-inflammatory and its hypocholesterolaemic effects ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Silybum marianum (milk thistle) and its main constituent silymarin (rich in flavolignans) ( 14 ) have been shown to reduce plasma and liver markers of inflammation in high-fat diet (HFD)-fed mice ( 15 ). Similarly, Taraxacum officinale (dandelion) extracts have been shown to reduce LPS-induced inflammation in endothelial cells ( 16 ) and macrophages ( 17 ) and have cholesterol-modulating effects in rodents ( 18 , 19 ) and type 2 diabetic patients ( 20 ). Likewise, Avena sativa (oat) is well-known for its anti-inflammatory and its hypocholesterolaemic effects ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…The extracts caused a dose-dependent inhibition of ADP induced aggregation, with a maximal inhibition of 85% observed at a concentration corresponding to 0.04 g dried root/ mL of human platelet-rich plasma (PRP)". Dandelion also reduces the concentration total cholesterol and serum triglycerides and in liver cells as cholesterol increases in the HDL fraction [Majewski et al 2020].…”
Section: Healing Propertiesmentioning
confidence: 99%
“…Moreover, dandelion leaf extracts impacted the lipid profile by diminishing triglycerides (0.44-fold), TC (0.73-fold), a lipoprotein combined index (0.32-fold), and a plasma atherogenic index (0.62-fold). Finally, it was suggested that dandelion leaf and petal phenolic fractions containing high contents of l-chicoric acid are valuable plant materials with potential beneficial antioxidant actions on a cardiovascular level [ 78 ].…”
Section: Dandelion ( Taraxacum Officinale L)—bmentioning
confidence: 99%